The Relationship Between Serum Cytokine Levels and the Degree of Psychosis and Cognitive Impairment in Patients With Methamphetamine-Associated Psychosis in Chinese Patients - Yang, Xue; Zhao, Hui; Liu, Xuebing; Xie, Qin; Zhou, Xiaoliang; Deng, Qijian; Wang, Gang (Frontiers in Psychiatry, 2020)
Background: Cytokine levels can be changed in methamphetamine (METH) use disorders (MUDs) and primary psychosis. The present study assessed serum levels of some kinds of interleukins (ILs) in METH-associated psychosis (MAP) and their relationships with psychotic symptoms and cognitive dysfunction. Methods: Serum IL-2R, IL-6, IL-8 and IL-10 levels were examined by chemiluminescence assays in MAP patients (n=119) and healthy controls (n=108). The Positive and Negative Syndrome Scale (PANSS) and Montreal Cognitive Assessment (MOCA) were administered. Results: Serum levels of IL-6 and IL-8 were significantly increased in MAP patients (all p<0.05). There was a negative relationship between IL-2R levels and PANSS positive (P) subscale scores (r=-0.193, p=0.035). IL-6, IL-8 and IL-10 levels were all negatively correlated with the naming, delayed recall and orientation subscores on the MOCA (r=-0.209, p=0.022; r=-0.245, p=0.007; r=-0.505, p<0.001, respectively). Conclusions: Our results indicate that immune disturbances are related to MAP and that IL-2R, IL-6, IL-8 and IL-10 are associated with the severity of psychotic symptoms and cognitive function impairment.